Paper money in Sheikh Ahmad Khatib Al-Minangkabawi's thought: A comparative and critical commentary - Muhammad Sholihin; Nurus Shalihin; Apria Putra (Islamic Economic Studies (IES), 2021)
Purpose The article examines Sheikh Ahmad Khatib Al-Minangkabauwi's initial concept of paper money, which in the early 20th century wrote Risala Raf'u Al-Iltibas. Design/methodology/approach This paper uses a qualitative approach based on the critical extraction analysis that can reveal a set of concepts related to the thoughts of Sheikh Ahmad Khatib Al-Minangkabauwi on paper money. Findings Through an attentive reading of Sheikh Ahmad Khatib Al-Minangkabawi, the authors can formulate several significant results: First, Ahmad Khatib Al-Minangkabawi applies two methods in studying critically on paper money, namely, the comparative law method and qiyas. Second, Ahmad Khatib believes that paper money has similarities with dinars and dirhams, namely its nominal value function. It is just that the existence of these values is different. Briefly, there are set law consequences for those who used paper money in economic activities, i.e. payment of zakāt on paper money applies when used as business capital. Research limitations/implications Sheikh Ahmad Khatib Al-Minangkabawi's work related to paper money is written heavily from the perspective of fiqh. Briefly, it is challenging to describe legal reasoning from work. As a result, articles are also thicker with fiqh analysis. Practical implications Sheikh Ahmad Khatib Al-Minangkabawi's view regarding paper money becomes the foundation for the theory of the value of money in Islam. However, it is rarely disclosed. In this regard, this paper can serve as the foundation of the value for money offered by scholars from Indonesia in the early 20th century. Social implications Money is not a commodity. Still, it must be positioned as capital to be productive. It finally becomes why trade is compelling and becomes the most practical reason for paying out zakāt. Originality/value It is not easy finding out articles that attempt to reveal the concept of classical ulemas or clerics from Indonesia relating to paper money. This article manages to identify that, and at the same time, becomes a novelty.
Keywords: A1; B1; G0; N0; Z1; 330; Comparative law; Fiat money; Money philosophy; Nominal value; Paper money; Qiyās